An Analytical Study in The English-Arabic Translation of Some Short Stories (The Peerian Journal, 2025)
Short story is one of the important topics in literary studies. The translation of short story is not easy. It has a number of difficulties that the translator may face during translation. This leads him/her to use a number of strategies that enable him/her to translate the literary texts efficiently. This research comprises three sections. Section one presents definitions of translation. Section two deals with the analytical levels of translation (lexical ,syntactic ,semantic ,phonological and stylistic levels).Section three investigates such levels in the English-Arabic translation of some short stories and analyze their implications in translation .Finally, the conclusions have been drawn.